Buscando a un Inca: la cripta de Topa Amaro - Martín Rubio, María del Carmen (2005)
The fratricidal fightings which took place in Tahuantinsuyo and the disturbance suffered by its people before the arrival of unknown men and animals hastened the falling of that state without any apparent resistance. But once surprise was overcome, Inca people laid siege to Cusco and, as they could not conquer the city, they took refuge in the Vilcabamba mountains, from where they started an uncomfortable guerrilla war trying to expel foreigners during almost forty years. This guerrilla war was successively led by four Huayna Capac descendant princes. Along this article, the performance and the death of Topa Amaro, the last governor in Vilcabamba, and the architectural evolution of the Qorikancha, the shrine in which the Inca was buried, are analyzed with additional evidence and works to find his grave are showed off.